Proof Of Criminal Acts In The Field Of Information And Electronic Transactions Judging From Law Number. 19 Of 2016 Concerning Information And Electronic Transactions - Sidabutar, Alcapon; Risdalina, Risdalina; Kumalasari M, Indra (International Journal of Educational Research & Social Sciences, 2024)
The aim of this research is to find out aboutEvidence in criminal acts of information and electronic transactions is reviewed from Law Number 19 of 2016 concerning Electronic Information and Transactions.Discussion Results: That,evidence in information crimes and electronic transactionsreferring to Article 184 of the Criminal Procedure Code. Where, the position of electronic evidence in proving criminal acts of information and electronic transactions is very important in accordance with the provisions of Article 184 of the Criminal Procedure Code, namely witness statements, expert statements, letters, instructions for defendant statements and the provisions of Law Number 19 of 2016 Article 5 of the ITE Law which regulates that electronic information, printed electronic documents are valid legal evidence.